VRE and VSE Bacteremia Outcomes in the Era of Effective VRE Therapy: A Systematic Review and Meta-analysis. (5th October 2015) - Prematunge, Chatura; MacDougall, Colin; Johnstone, Jennie; Adomako, Kwaku; Lam, Freda; Robertson, Jennifer; Garber, Gary
Abstract : BACKGROUND: Prior data suggest that vancomycin-resistant Enterococcus (VRE) bacteremia is associated with worse outcomes than vancomycin-sensitive Enterococcus (VSE) bacteremia. However, many studies evaluating such outcomes were conducted prior to the availability of effective VRE therapies. OBJECTIVE: To systematically review VRE and VSE bacteremia outcomes among hospital patients in the era of effective VRE therapy. METHODS: Electronic databases and grey literature published between January 1997 and December 2014 were searched to identify all primary research studies comparing outcomes of VRE and VSE bacteremias among hospital patients, following the availability of effective VRE therapies. The primary outcome was all-cause, in-hospital mortality, while total hospital length of stay (LOS) was a secondary outcome. All meta-analyses were conducted in Review Manager 5.3 using random-effects, inverse variance modeling. RESULTS: Among all the studies reviewed, 12 cohort studies and 1 case control study met inclusion criteria. Similar study designs were combined in meta-analyses for mortality and LOS. VRE bacteremia was associated with increased mortality compared with VSE bacteremia among cohort studies (odds ratio [OR], 1.80; 95% confidence interval [CI], 1.38–2.35; I 2 =0%; n=11); the case-control study estimate was similar, but not significant (OR, 1.93; 95% CI, 0.97–3.82). LOS was greater for VRE bacteremia patients than for VSE bacteremia patients (mean difference, 5.01 days; 95% CI, 0.58–9.44]; I 2 =0%; n=5). CONCLUSIONS: Despite the availability of effective VRE therapy, VRE bacteremia remains associated with an increased risk of in-hospital mortality and LOS when compared to VSE bacteremia. Infect. Control Hosp. Epidemiol. 2015;37(1):26–35